ChemInform Abstract: Highly Active Aluminum Catalysts for the Formation of Organic Carbonates from CO2 and Oxiranes. Issue 32 (12th August 2014) - Whiteoak, Christopher J.; Kielland, Nicola; Laserna, Victor; Castro‐Gomez, Fernando; Martin, Eddy; Escudero‐Adan, Eduardo C.; Bo, Carles; Kleij, Arjan W.
Abstract Al(III) complexes of amino‐tris(phenolate) ligand scaffolds (I) are prepared to attain effective Lewis acidic catalysts.